2010
DOI: 10.1074/jbc.m110.161802
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Activation of PSI-7851 and Its Diastereoisomer PSI-7977

Abstract: A phosphoramidate prodrug of 2-deoxy-2-␣-fluoro-␤-Cmethyluridine-5-monophosphate, PSI-7851, demonstrates potent anti-hepatitis C virus (HCV) activity both in vitro and in vivo. PSI-7851 is a mixture of two diastereoisomers, PSI-7976 and PSI-7977, with PSI-7977 being the more active inhibitor of HCV RNA replication in the HCV replicon assay. To inhibit the HCV NS5B RNA-dependent RNA polymerase, PSI-7851 must be metabolized to the active triphosphate form. The first step, hydrolysis of the carboxyl ester by huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
313
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 268 publications
(323 citation statements)
references
References 34 publications
10
313
0
Order By: Relevance
“…PSI-7977, the Sp isomer, has better activity than PSI-7976 (Rp isomer) in replicon-based HCV inhibition assays (38) and is currently in phase 3 clinical trials. The 5=-triphosphate metabolite of PSI-7977, PSI-7409, inhibits HCV replication by serving as a nonobligate chain terminator (30). Cross-resistance studies have shown that PSI-7977 and PSI-7409 had reduced activity against GT 1b replicons and NS5B polymerase containing the S282T amino acid alteration, respectively (18,38).…”
mentioning
confidence: 99%
“…PSI-7977, the Sp isomer, has better activity than PSI-7976 (Rp isomer) in replicon-based HCV inhibition assays (38) and is currently in phase 3 clinical trials. The 5=-triphosphate metabolite of PSI-7977, PSI-7409, inhibits HCV replication by serving as a nonobligate chain terminator (30). Cross-resistance studies have shown that PSI-7977 and PSI-7409 had reduced activity against GT 1b replicons and NS5B polymerase containing the S282T amino acid alteration, respectively (18,38).…”
mentioning
confidence: 99%
“…The history and potential of this compound and closely related compounds have recently been published and these papers should be consulted by interested readers. [40][41][42][43][44] It should also be mentioned that significant numbers of antiviral drugs against HIV are now delivered as preadjusted combinations of reverse transcriptase, integrase and protease inhibitors, which have the potential to reduce this disease to chronic status. An example uses emtricitabine (84) and tenofovir (82) plus the non-nucleoside reverse transcriptase inhibitor (rilpivirine; structure not shown as not a nucleoside …”
Section: Antiviral Agents Based On Nucleosidesmentioning
confidence: 99%
“…Among the nucleoside/nucleotide analogs, RG7128 (the prodrug of PSI-6130, ␤-D-2Ј-fluoro-2Ј-C-methylcytidine) is the most advanced anti-HCV nucleoside and is currently in phase IIb clinical studies. So far, results from the clinical studies showed that RG7128 is generally safe and effective in reducing the viral loads for genotype 1, 2, 3, and 4 HCV-infected patients when it is combined with SOC, with no resistance-related breakthrough (16,21,27,37).More recently, we reported results of in vitro studies characterizing PSI-7851 and PSI-7977 (the single Sp isomer of PSI-7851), phosphoramidate prodrugs of ␤-D-2Ј-fluoro-2Ј-Cmethyluridine 5Ј-monophosphate (30,45,48). While RG7128 was designed to improve the pharmacokinetic profile of PSI-6130, PSI-7851 and PSI-7977 were synthesized to bypass the nonproductive first phosphorylation step, as the corresponding nucleoside analog was incapable of being converted to the monophosphate form.…”
mentioning
confidence: 99%
“…More recently, we reported results of in vitro studies characterizing PSI-7851 and PSI-7977 (the single Sp isomer of PSI-7851), phosphoramidate prodrugs of ␤-D-2Ј-fluoro-2Ј-Cmethyluridine 5Ј-monophosphate (30,45,48). While RG7128 was designed to improve the pharmacokinetic profile of PSI-6130, PSI-7851 and PSI-7977 were synthesized to bypass the nonproductive first phosphorylation step, as the corresponding nucleoside analog was incapable of being converted to the monophosphate form.…”
mentioning
confidence: 99%